Program Pengembangan Budaya KewirausahaanDi Perguruan Tinggi: Pelaksanaan Inkubator Wirausaha BarDi Universitas Gadjah Mada, Yogyakartau - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRAK The aim of the program is to support the Directorate General of Higher Education regarding the socialization of entrepreneurship spirit to students on New Entrepreneurship Incubator Program (INWUB) was participated by students and fresh graduates who are learning by doing to practice geplak, tofu and tempe gembus fillet production. In addition to production aspects, students also learned how to create market networking and management skill. Incubator program is expected to have more benefit to participants (students and fresh graduates), lecturers, institution, and community. So, this program must be supported or motivated to develop entrepreneurship spirit of students. Keywords: incubator, entrepreneurship spirit, geplak, tofu, tempe gembus.